(untitled) (Applied Biological Research, 2019)
Sunflower (Helianthus annuus L.), an important edible oil seed crop, is prone to severe attack by necrosis, Alternaria leaf spot and powdery mildew diseases which lead to poor seed germination and loss of seedling vigour and yield. The present study was conducted for 3 consecutive years with the aim to manage these foliar diseases under field conditions through seed priming (bio or chemo) followed by fungicide/insecticide spray. The result revealed that among the treatments tested, seed priming with carbendazim @ 2 g + thiamethoxam @ 4 g kg-1seeds followed by foliar spray of propiconazole @ 0.1% + thiamethoxam @ 0.04% twice (30 and 45 days after sowing) gave effective control of necrosis (2.27%), leaf spot (19.6 PDI) and powdery mildew (17.94 PDI) diseases with seed yield increase (1443 kg ha-1) over control. This was followed by Trichoderma viride priming which recorded 7.1% necrosis, 38 PDI of leaf spot and 36.31 PDI of powdery mildew. Seed bio- or chemo-priming promoted higher and uniform seed germination under field conditions. Seed priming with carbendazim @ 2 g kg-1 + thiamethoxam @ 4 g kg-1 along with two foliar sprays of propiconazole @ 0.1% + thiamethoxam @ 0.04% (30 and 45 DAS) were effective.